Communication, forgiveness and morbidity in young adults involved in a romantic relationship - Pereira, M. Graça (2022)
This study examined the direct and indirect effects of communication patterns and forgiveness on physical and psychological morbidity, among young adults involved in a romantic relationship. Participants were 298 students, currently involved in a heterosexual romantic relationship, from a large university in the United States, who completed the Tendency to Forgive Scale, the Communication Patterns Questionnaire, and the Rotterdam Symptom Checklist. Physical morbidity was directly predicted by mutuality communication. Destructive communication had an indirect effect on physical and psychological morbidity, via forgiveness. However, the indirect connection between destructive communication and psychological morbidity was only significant for female partners. Teaching constructive communication skills may be a key factor for interventions addressed to young adults in romantic relationships, in order to promote forgiveness, due to its potential positive influence in physical and psychological well-being.